Zinc-Mediated Template Synthesis of Fe-N-C Electrocatalysts with Densely Accessible Fe-Nx Active Sites for Efficient Oxygen Reduction - Chen, Guangbo; Liu, Pan; Liao, Zhongquan; Sun, Fanfei; He, Yanghua; Zhong, Haixia; Zhang, Tao; Zschech, Ehrenfried; Chen, Mingwei; Wu, Gang; Zhang, Jian; Feng, Xinliang (Advanced Materials, 2020)
Owing to their earth abundance, high atom utilization, and excellent activity, single iron atoms dispersed on nitrogen-doped carbons (Fe-N-C) have emerged as appealing alternatives to noble-metal platinum (Pt) for catalyzing the oxygen reduction reaction (ORR). However, the ORR activity of current Fe-N-C is seriously limited by the low density and inferior exposure of active Fe-Nx species. Here, a novel zinc-mediated template synthesis strategy is demonstrated for constructing densely exposed Fe-Nx moieties on hierarchically porous carbon (SA-Fe-NHPC). During the thermal treatment of 2,6-diaminopyridine/ZnFe/SiO2 complex, the zinc prevents the formation of iron carbide nanoparticles and the SiO2 template promotes the generation of hierarchically pores for substantially improving the accessibility of Fe-Nx moieties after subsequent leaching. As a result, the SA-Fe-NHPC electrocatalysts exhibit an unprecedentedly high ORR activity with a half-wave potential (E1/2) of 0.93 V in a 0.1 m KOH aqueous solution, which outperforms those for Pt/C catalyst and state-of-the-art noble metal-free electrocatalysts. As the air electrode in zinc–air batteries, the SA-Fe-NHPC demonstrates a large peak power density of 266.4 mW cm−2 and superior long-term stability. Therefore, the developed zinc-mediated template synthesis strategy for boosting the density and accessibility of Fe-Nx species paves a new avenue toward high-performance ORR electrocatalysts.
CRIS-Team Scopus Importer:2023-03-20
Keywords: accessible active sites; Fe-N-C catalysts; oxygen reduction reaction; zinc-mediated synthesis; Zn–air batteries